Human Skin‐Derived Precursor Cells Are Poorly Immunogenic and Modulate the Allogeneic Immune Response. (15th July 2014) - De Kock, Joery; Meuleman, Philip; Raicevic, Gordana; Rodrigues, Robim M.; Branson, Steven; Meganathan, Kesavan; De Boe, Veerle; Sachinidis, Agapios; Leroux-Roels, Geert; Vanhaecke, Tamara; Lagneaux, Laurence; Rogiers, Vera; et al.
Abstract Human skin‐derived precursors (hSKPs) are multipotent somatic stem cells that persist within the dermis throughout adulthood and harbor potential clinical applicability. In this study, we investigated their immunogenicity and immunosuppressive features, both in vitro and in vivo. As such, this study provides a solid basis for developing their future clinical applications. We found that hSKPs express HLA‐ABC molecules, but not HLA‐DR, rendering them poorly immunogenic. Using a coculture set‐up, we could further demonstrate that hSKPs inhibit the proliferation of allogeneic activated T cells and alter their cytokine secretion profile, in a dose‐dependent manner. Cotransplantation of hSKP and human peripheral blood leukocytes (PBL) into severe combined immune‐deficient mice also showed a significant impairment of the graft‐versus‐host response 1 week post‐transplantation and a drastic increase in survival time of 60%. From a mechanistic point of view, we found that hSKPs require cell contact as well as secretion of soluble inhibitory factors in order to modulate the immune response. The expression/secretion levels of these factors further increases upon inflammation or in the presence of activated T cells. As such, we believe that these features could be beneficial in a later allogeneic clinical setting, because rejection of engrafted allogeneic hSKP might be delayed or even avoided due to their own promotion of a tolerogenic microenvironment. Stem Cells2014;32:2215–2228